Flight routes performance improvement for garuda indonesia using balanced scorecard - Ariobimo, Adhityo; Hanafi, Muhammad (The Indonesian Journal of Business Administration, 2019)
Abstract. Garuda Indonesia is the national flag carrier of Indonesia. The airline operates flights to over 14 countries and 133 destinations worldwide. As a service company, Garuda Indonesia is focusing its main business on air transport that provides full service. In 2017, Garuda Indonesia had experienced a loss of US$ 155 million. It has also found out that there were five routes from Jakarta in 2017 that are underperformed with market share below 20 percent, which are also didn’t make profit because the total costs from those specific routes are higher than the revenues that are generated. There are two problems that is addressed in this study. First is the cause of the five routes to have a low market share. Second is the operation strategy to improve the performance of Garuda Indonesia. This research is utilizing qualitative methodology with conducting in-depth interview with four interviewees from corporate planning and business performance unit. Furthermore, secondary data were also gathered from the company’s internal data. This research then analyzed to examine the root cause of the problem, thus formulating the strategies for the root causes. In formulating the strategies, balanced scorecard framework is used to translate the strategies into KPI and strategic initiatives. Balanced scorecard framework is used to help the research as this method offers many advantages including to translate the abstract goals into action items that can be monitored. It also provides objective measure of the current situation and can help the company in improving the condition of the company. Overall, BSC determines the knowledge, skill and systems that employees will need to innovate and build the right strategic capabilities that deliver specific value to the market. In the end, it will lead to higher shareholder value. It is found out that there are 4 root causes that proves significant in causing the routes to have low market share. Based on the 4 root causes, 8 strategies are formulized with Balanced Scorecard framework which then formed 13 KPIs and 21 strategic initiatives for Corporate Planning division.Keyword: Aviation, Airline, Performance Measurement, Performance Management System, Balanced Scorecard, KPI